PENGEMBANGAN INSTRUMEN PENILAIAN KINERJA DENGAN PENDEKATAN ILMIAH PADA PEMBELAJARAN BERBASIS KEGIATAN EKSPERIMEN KALORIMETER (UPEJ Unnes Physics Education Journal, 2017)
This research aims to develop an instrument of performance assessment with valid, reliable, effective, and feasible criteria. This research used Research and Development (R&D) method. The procedure includes: problem and identification problem, collecting data, product design, product design validation, product design revision, limited-scale product trial, product revision I, product application trial, product revision II and final product. Result of the research shows that performance assessment instrument that developed using scientific approach that consist of using tools and material activity, observing activity, write data observation, and analyze data observation. Performance assessment instrument is stated valid with the mean percentage score of design by two validator 97.92% and the evaluation 100%. Instrument is stated reliable, with coefficient of reliability in average rating of the three raters are 0.9378 and coefficient of reliability in average rating for each rater is 0.8341. Instrument is stated effective with the percentage of the difference assessment is 1.66%. Instrument is stated very feasible with the mean percentage score 94.53%..